2021
DOI: 10.1177/2325967121999401
|View full text |Cite
|
Sign up to set email alerts
|

Game Spacing and Density in Relation to the Risk of Injuries in the National Hockey League

Abstract: Background: Ice hockey has significant workload demands. Research of other sports has suggested that decreased rest between games as well as an increased workload may increase the risk of injuries. Purpose: To evaluate whether condensed game schedules increase the frequency and severity of injuries in the National Hockey League (NHL). Study Design: Descriptive epidemiology study. Methods: Data were obtained from publicly available online sources on game schedules and injuries for all NHL teams for the 2005-200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The 2019-2020 playoffs had an extraordinarily high number of exposures per week with less recovery time between games. Decreases in game spacing have previously been proven to increase the risk of injury in the NHL [ 17 ]. Additionally, because we found a significant correlation between playoff density and injury, it is likely that the condensed schedule played a part in the increased injury rate during the 2019-20 playoffs.…”
Section: Discussionmentioning
confidence: 99%
“…The 2019-2020 playoffs had an extraordinarily high number of exposures per week with less recovery time between games. Decreases in game spacing have previously been proven to increase the risk of injury in the NHL [ 17 ]. Additionally, because we found a significant correlation between playoff density and injury, it is likely that the condensed schedule played a part in the increased injury rate during the 2019-20 playoffs.…”
Section: Discussionmentioning
confidence: 99%
“…However, they do not align with studies of the National Hockey League (NHL) and National Basketball Association (NBA), which found an increased risk of injury with schedule condensation and away games on consecutive days, respectively. 5 , 27 This underscores the unique nature of the NFL schedule among American team sports, in which teams invariably play 1 game per week, half of which are at home, and therefore travel a maximum of once per week for half of the season. In contrast, an NBA or NHL team may play on consecutive days and multiple times per week in different cities.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the current study was to determine the relationship between scheduling factors and injury rates among professional athletes in the NFL. Based on the results of previous studies among other professional sports, 5 , 27 we hypothesized that higher cumulative travel distance, playing overseas games, having a bye week earlier in the season, and an expansion of the regular season would be associated with higher injury rates.…”
mentioning
confidence: 99%
“…In the National Hockey League, it is for example normal routine to compete in four games weekly, spending large amounts of time traveling and leaving limited time to restore physiological homeostasis, which may increase the predisposition to injuries and lead to performance deteriorations. 8 It has previously been demonstrated that muscle force production in university level ice hockey players is impaired by up to 30% during a weekly cycle of games and training. 9 In particular, the force production obtained by low-frequency (20 Hz) electrical stimulation of the muscle surface was reduced postexercise and during recovery, a common phenomenon determined "prolonged lowfrequency force depression".…”
Section: Introductionmentioning
confidence: 99%
“…This is highly relevant in modern elite ice hockey as players endure tightly congested in‐season game schedules and during cup tournaments, where games are often played on consecutive days interspersed with less than 24 h of recovery. In the National Hockey League, it is for example normal routine to compete in four games weekly, spending large amounts of time traveling and leaving limited time to restore physiological homeostasis, which may increase the predisposition to injuries and lead to performance deteriorations 8 …”
Section: Introductionmentioning
confidence: 99%